2021
DOI: 10.1093/jamia/ocab119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of implementing electronic prior authorization on medication filling in an electronic health record system in a large healthcare system

Abstract: Objective Medications frequently require prior authorization from payers before filling is authorized. Obtaining prior authorization can create delays in filling prescriptions and ultimately reduce patient adherence to medication. Electronic prior authorization (ePA), embedded in the electronic health record (EHR), could remove some barriers but has not been rigorously evaluated. We sought to evaluate the impact of implementing an ePA system on prescription filling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…EPA with real-time status updates is a feature widely requested by providers, though a previous study showed it did not improve medication fill rate and adherence. 23,24 In our experience with EPA, the key to successful implementation is developing a clear and coordinated workflow. The 3 hospitals using EPA established a system in which each time a medication requiring PA was prescribed, a message was sent to a queue in the EHR for clinical pharmacists to process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EPA with real-time status updates is a feature widely requested by providers, though a previous study showed it did not improve medication fill rate and adherence. 23,24 In our experience with EPA, the key to successful implementation is developing a clear and coordinated workflow. The 3 hospitals using EPA established a system in which each time a medication requiring PA was prescribed, a message was sent to a queue in the EHR for clinical pharmacists to process.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing use of EHRs, interventions embedded within the EHR have shown potential to improve the discharge process on a systemic level. 4,22,23 At an 8-hospital system, a transition-in-care (TIC) team composed of pharmacists and nurses followed up with patients after discharge to identify and help resolve any postdischarge barriers. The recurrent issues identified by the TIC team from patients' responses prompted the creation of system-wide EHR interventions to address the most common barriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For inpatients transitioning at discharge, outpatient pharmacy “meds to bed” services can play a vital role in ensuring the patient receives the appropriate CDI therapy before being discharged from the hospital [ 42 ]. Additionally, antimicrobial stewardship programs in the inpatient and outpatient setting can assist with ensuring continuity of care and anticipating challenges due to cost and access, including prior authorization requirements, which certainly influence subsequent adherence [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Though some healthsystems have implemented software aimed at increasing visibility of medication costs, these predictions do not always provide accurate or real-time data. [18][19][20] The American Medical Association and physicians have encouraged implementing price transparency into the EHR, so long as it is meaningful and actionable. 17,21 Given the high cost of many maintenance inhalers limits patient access to therapy, ensuring that prescribed inhaler therapy is covered by insurance and affordable to patients prior to discharge could reduce primary and secondary nonadherence 22 and improve patient satisfaction.…”
Section: Inhaler Therapy Recommendationsmentioning
confidence: 99%